2022
DOI: 10.1002/ctm2.854
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase α1 phosphorylates PHD2 to maintain systemic iron homeostasis

Abstract: Background Iron is essential for all mammalian life, and either a deficiency or excess of iron can cause diseases. AMP‐activated protein kinase (AMPK) is a critical regulator of metabolic homeostasis; however, it has not been established whether AMPK regulates iron metabolism. Methods Iron, hepcidin and ferroportin levels were examined in mice with global and hepatocyte‐specific knockout of AMPKα1 and AMPKα2. Primary AMPKα1 or AMPKα2 deleted hepatocytes were isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Although its most recognized role is that of a 'HIF regulator', we previously found that PHD2 can activate calmodulin-dependent protein kinase (CaMKK) β upstream of AMP-activated protein kinase (AMPK) and thereby protect against hypoxia-induced effects in cardiomyocytes; phosphorylated AMPK is a key factor in cell survival as it regulates energy metabolism [15,23]. This hypothesis has also been confirmed by other researchers studying systemic iron homeostasis [24]. Thus, we speculated that in diabetic wounds, PHD2 may promote wound repair by regulating AMPK.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although its most recognized role is that of a 'HIF regulator', we previously found that PHD2 can activate calmodulin-dependent protein kinase (CaMKK) β upstream of AMP-activated protein kinase (AMPK) and thereby protect against hypoxia-induced effects in cardiomyocytes; phosphorylated AMPK is a key factor in cell survival as it regulates energy metabolism [15,23]. This hypothesis has also been confirmed by other researchers studying systemic iron homeostasis [24]. Thus, we speculated that in diabetic wounds, PHD2 may promote wound repair by regulating AMPK.…”
Section: Discussionmentioning
confidence: 60%
“…It is well known that AMPK is the main regulator of metabolic homeostasis and as a cellular energy sensor, it is the guardian of the energy state of the cell [24,35]. AMPK is a key regulator of energy homeostasis, and coordinates adaptive responses in metabolic states depleting ATP such as hypoxia, ischemia/reperfusion, and exercise [36].…”
Section: Plos Onementioning
confidence: 99%
“…The KEGG enrichment analysis revealed that the DEGs were mainly enriched in the AMPK and PPAR signaling pathways. The role of AMPK signaling pathway in regulating energy homeostasis is related to its effects on glucose and lipid metabolism, as well as on mitochondrial biogenesis and function [33]. The PPAR signaling pathway is mainly involved in regulating fatty acid metabolism, and cell proliferation and differentiation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Cheng Wang and colleagues postulate the coexistence of PHD2 and AMPK within the same complex. AMPKα1 phosphorylates PHD2, rendering it inactive and curtailing the PHD2-mediated hydroxylation and degradation of HIF-1α ( Wang et al, 2022b ). The profound interrelation between AMPK-dependent and -independent regulation of HIF-1α, as well as the potential cross-linkage between these pathways, remains a terrain ripe for further exploration ( Figure 2 ).…”
Section: The Intrinsic Relationship Between Hypoxia and Poor Neovascu...mentioning
confidence: 99%